SOCIO-ECONOMIC FACTORS AFFECTING FOOD SECURITY AMONG THE ELDERLY. A CRITICAL LITERATURE REVIEW - Njeri, Arianna (Journal of Food Sciences, 2021)
Purpose: Mobile technologies provide an affordable and easily accessible technology that lecturers can use effectively to assist students with their studies. The general objective of the study was to evaluate socio-economic factors affecting food security among the elderly. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: From the study findings, it is concluded that the households of the elderly persons are faced with abject poverty due to the household structures they live in, which lack food storage facilities hindering food utilization. The elderly persons are faced with health challenges that hinder them from accessing adequate and appropriate foods. They also are not able to use the available types of food due to the ailments they suffer. Elderly persons are faced by various levels of food insecurity due to the deteriorating strength and vulnerability that comes handy with aging. Farming practices by elderly persons depict that they mainly use manual labour limiting their food production. The elderly persons food utilization that entails enlightenment on food production based on food storage, feeding habits and farming methods have lowered food production thus food insecurity. Recommendations: The study recommended that there should be established programmes that provide homes for the aged to cater for the elderly persons who live alone, sickly and too aged to undertake their daily domestic duties. In addition feeding programmers in households with elderly persons should be formulated and implemented. Relatives should be encouraged to follow up on the wellbeing of their aging parents and organize to employ care givers to keep up domestic duties that may be making it difficult for the elderly to access food. The ministry of special programmes should consider provision of relief food to households with the elderly persons who suffer severe food insecurity. They should also collaborate with the ministry of education in ensuring children who are under the care of aged people have a school feeding programme to provide at least a meal for them at school.